Pemanfaatan Teknologi Surveillance Car - Purba, Amanda Averina (Police Studies Review, 2020)
The development of the era that is currently entering industrial revolution 4.0 requires the Police to provide maximum service to the community. In line with the 7 priority programs of the National Police Chief, particularly on point 2, which is the strengthening of national security and order which includes early detection, Intelkam's technical functions as a unit of police functions that have the responsibility for early detection innovate by presenting special intelligence tools as an effort to increase capabilities, one of which is the Surveillance Car . The purpose of this research is to describe the utilization of Surveillance Car technology by the Intelligence Unit and find factors that influence the use of the Surveillance Car technology by the Intelligence Unit. This study uses a qualitative approach with descriptive analysis techniques. Theories and concepts used are management theory, consisting of elements of management theory and seven steps operational management, the concept of utilizing information technology. The findings of this study are the lack of knowledge and ability of human resources in mastering technology and the lack of utilization of Surveillance Car technology by the Intelligence Unit which is caused by many inhibiting factors. It was concluded that the utilization of Surveillance Car technology by Sat Intelkam was still not optimal and there were still factors that inhibited the use of the technology.